2013
DOI: 10.1007/s10113-013-0464-0
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots of recent drought in Asian steppes

Abstract: The present study aims to identify hotspots on the Asian steppe that were vulnerable to widespread drought events in the Northern Hemisphere during 1999-2002, using newly proposed indices of vegetation response (sensitivity and resilience) to drought. Drought sensitivity is defined as vegetation response to decreased precipitation from pre-drought to drought phases, and resilience is defined as response to increased precipitation from drought to post-drought phases. Thus, the sensitivity and resiliency indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The observed data showed that annual plant species increased more than perennial ones after drought years [ Shinoda et al, ]. Numerous studies have shown that grassland degradation has increased [ Mandakh et al , ; Nandintsetseg and Shinoda , ] and at the same time plant species composition has continually declined; moreover, shifts in from perennial to annual species have been induced by climate change (drought) [ Shinoda et al, ] and overgrazing in the Mongolian grasslands during recent decades [e.g., Jigmed , ; Tuvshintogtoh and Ariunbold , ; Hilker et al , 2013]. The model is unable to consider such changes in species and functional diversity of the plant community [e.g., Parton et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The observed data showed that annual plant species increased more than perennial ones after drought years [ Shinoda et al, ]. Numerous studies have shown that grassland degradation has increased [ Mandakh et al , ; Nandintsetseg and Shinoda , ] and at the same time plant species composition has continually declined; moreover, shifts in from perennial to annual species have been induced by climate change (drought) [ Shinoda et al, ] and overgrazing in the Mongolian grasslands during recent decades [e.g., Jigmed , ; Tuvshintogtoh and Ariunbold , ; Hilker et al , 2013]. The model is unable to consider such changes in species and functional diversity of the plant community [e.g., Parton et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Multidisciplinary approaches to key linkages of complex natural and human systems have revealed that climate change impacts on such systems are often nonlinear, having a threshold or tipping point across which a catastrophic (and potentially nonresilient) change may occur in the system [see, e.g., Scheffer et al ., ]. For example, on the regional‐continental scale, such changes or thresholds are detected in the response of vegetation to drought [ Shinoda et al ., ], land‐surface to wind erosion or dust emission (i.e., threshold wind speed) [ Kurosaki et al ., ], and livestock mortality to dzud [ Tachiiri et al ., ; Tachiiri and Shinoda , ]. The satellite‐derived threshold wind speed was used to produce a novel semi‐real‐time wind erodibility (i.e., soil susceptibility to wind erosion) map available for a dust early warning system [ Kimura and Shinoda , ].…”
Section: Dryland Expansion Desertification and Adaptationmentioning
confidence: 99%
“…Shinoda et al . [] identified hot spots that exhibited nonresilient vegetation degradation after a multiyear megadrought in the Asian steppe using newly developed indices related to sensitivity and resilience (Figure ). Temperate grasslands surrounding the desert dust source regions are likely to be sensitive to the ongoing and projected expansion of Asian drylands and are significant or potentially significant dust sources [ Shinoda et al ., ; Nandintsetseg and Shinoda , ].…”
Section: Dryland Expansion Desertification and Adaptationmentioning
confidence: 99%
See 2 more Smart Citations